The Effect of the Model of Experiential Learning Model Towards Students' Science Process Skill in Natural Science Learning at SD Pembangunan Laboratorium Padang State University - Belia, Stavini (The Future of Education Journal, 2022)
This research is motivated by the absence of optimal scientific or practical activities in science learning. This study aims to determine how the effect of the experiential learning model on students' science process skills in learning science at SD Pembangunan Lab UNP Padang. The population quasi-experimental with randomized control group only design is all grade students of SD Pembangunan Lab UNP Padang. The sampling technique was done by purposive sampling. Analysis using t-test at 0.05 significance level for cognitive, affective, and psychomotor learning achievement. The results showed that in the cognitive aspect, the average final test score for the experimental class was 65.41 while the control class was 59.25. In the affective domain, the average value of the experimental class is 76.05 while the control class is 72.96 and in the psychomotor domain, the average value of the experimental class is 77.72 while the control class is 74.33. Based on the hypothesis test, namely the similarity test of the t-count results for the three domains in the rejection area of Ho, it means that there is a significant difference in learning outcomes between the experimental class and the control class. This is believed to be due to the influence of the application of learning using the experiential learning model on students' science process skills in science learning at SD Pembangunan Lab UNP Padang